Vibrational Spectroscopic Investigation of 2,2'-Bipyridine Adsorbed on Loughlinite from Aqueous Suspensions - AKYUZ*, S.; AKYUZ, T. (Asian Journal of Chemistry, 2009)
The adsorption of 2,2'-bipyridine onto loughlinite (Na-sepiolite) hasbeen investigated by FT-IR and micro-Raman spectroscopy. Spectroscopicresults indicate the formation of monoanionic surface species.Most of the adsorbed molecules are incorporated in the channels of theclay structure and coordinated to Lewis acidic centers directly or indirectlythrough water molecules.